The Role of Land Use and Housing Laws in Mitigating Climate Change Effects - Gourav Kumar Sharma (International Journal of Land, 2024)
This study explores the crucial role of land use and housing laws in mitigating the effects of climate change, focusing on how urban planning, zoning regulations, and building codes can drive sustainable, climate-resilient development. As cities worldwide face the dual challenges of rapid urbanization and escalating climate risks, land use policies offer significant potential for reducing greenhouse gas emissions and enhancing adaptation to climate impacts. The paper examines strategies such as transit-oriented development (TOD), mixed-use zoning, and energy-efficient building codes, all of which can reduce carbon footprints, lower transportation emissions, and promote more sustainable living environments. Additionally, it highlights the importance of integrating green infrastructure, such as parks and green roofs, into urban planning to mitigate urban heat islands and manage stormwater effectively. The study also addresses the intersection of equity and climate policy, stressing the need for affordable housing laws that ensure vulnerable communities benefit from climate adaptation measures. By synthesizing global examples and policy frameworks, the research underscores how land use and housing laws can provide both immediate and long-term solutions for reducing the environmental impact of urban areas. Ultimately, the study advocates for a holistic approach to urban development that aligns climate change mitigation with social, economic, and environmental goals, fostering cities that are not only sustainable but resilient to future climate challenges.
Keywords: Environmental; Land use laws; economic; green spaces; social